Polarization‐Engineered Noninterleaved Metasurface for Integer and Fractional Orbital Angular Momentum Multiplexing. Issue 1 (22nd November 2020) - Zhang, Kuang; Yuan, Yueyi; Ding, Xumin; Li, Haoyu; Ratni, Badreddine; Wu, Qun; Liu, Jian; Burokur, Shah Nawaz; Tan, Jiubin
Abstract: Vortex beam carrying orbital angular momentum (OAM) has been widely explored in optical and microwave regions attributed to its potential characteristics in communication systems. For circular polarization incidence, Pancharatnam–Berry (PB) phase is a direct resource to generate phase gradient along the azimuthal direction required by specific OAM mode. The main drawback of PB phase is that it only affects cross‐polarized fields and keeps the copolarized part unmodulated. Here, a paradigm‐shift perspective of noninterleaved metasurfaces is proposed, which can simultaneously generate separate multiple integer and fractional OAM modes occupying both copolarized and cross‐polarized output channels. The scheme is validated by a series of experimental demonstrations in the microwave regime. By adjusting the polarization states of both input and receiving ends, different integer and fractional OAM modes are demonstrated in the full transmission channels. The results offer a unique recipe to enhance information capacity of metasurfaces and trigger versatile electromagnetic (EM) wave function integrations for advanced compact systems. A variety of applications can be readily expected in spin‐selective optics, spin‐Hall metadevices, and multitask metasurfaces operating in both reflection and transmission modes. Abstract : A general scheme is proposed to construct noninterleaved metasurface for generating multiple integer and fractional orbital angular momentum modes through altering the polarization state of the input and output ends. The co‐ and cross‐polarized output channels are completely utilized based on geometric and propagation phase modulations, and the transmitted energy is fully applied to implement five distinct vortex wavefronts.